The rise of green extractivism : extractivism, rural livelihoods and accumulation in a climate-smart world - Bruna, Natacha (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"The Rise of Green Extractivism tackles the understudied interconnections between extractivism and climate-smart policies and their implications for rural livelihoods, both theoretically and empirically. This new variation of extractivism arises as an innovative way in which capitalist production and accumulation unfolds and constitutes a convenient analytical tool in today's focus on reducing or compensating for emissions. The book consolidates "extractivism" as a theoretical framework that fully challenges contemporary capitalism's dynamics, particularly in the current global environmental crisis. It explores new dynamics of accumulation, resource grabbing and legitimation strategies. These are approached as mechanisms of appropriation of resources that produce social, economic and ecological implications to be considered in the current agrarian question debates. By analysing the implementation and outcomes of green policies, the author shows that new strategies of capital accumulation arise through the creation of new commodities, markets, vehicles of accumulation and ways of legitimising capital accumulation. A new and "greener" frontier of accumulation is constituted. These emerging processes of commodification bring along new waves of expropriation that further cut into the necessary consumption of rural populations. Insights from empirical cases explored in this book show how this new wave of green investments and projects, directly linked to climate change concerns, are further expropriating livelihoods and fuelling capital accumulation in the name of the fight against climate change. This book will be of great interest to students, scholars and researchers of political economy, globalisation, development studies, economics, political ecology, agrarian studies and environmental studies. It will also inform and provide policymakers with evidence-based insights into their decision-making process when designing and implementing climate change mitigation and adaptation policies, especially in developing countries"--
The theoretical underpinnings of the intersection of extractivism and climate change solutions -- Historical background and the role of the state -- From a threat to an opportunity : climate change as the new frontier of accumulation -- Land of plenty, land of misery : synergistic resource grabbing in Mozambique -- The rise of green extractivism -- Understanding livelihoods, social reproduction and reactions.
Keywords: Rural development -- Environmental aspects; Sustainable development; Eminent domain; Land use; Natural resources; POLITICAL SCIENCE / General